Contribution of Modelling and Analysis of Wireless Communication for Safety Related Systems with Bluetooth Technology - Pendli, Pavan Kumar; Friesen, Helena (Kassel University Press GmbH_Legacy, 2014)
Key Terms: wireless, communication, bluetooth, safety